1991
DOI: 10.1002/er.4440150104
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characteristics of packed bed storage system

Abstract: The thermal behaviour of a packed bed storage system charged with hot air is modelled using two partial differential equations representing the energy conservation in the air and solid phases constituting the bed. These two equations are coupled through the heat exchange process between the two phases.A fully implicit numerical scheme based on forward, upwind and central differencing for the time, first and second space derivatives, respectively, is used to solve the modelling equations. Marching technique is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Recalling equation (6) , it is seen that the bulk density of a material is a function of its particle density as well as its porosity . Relatedly, it has been reported that the heat load in a packed bed (relative to a set temperature) is increased through use of materials with greater particle density ( Aly and El-Sharkawy, 1990 ; Elouali et al, 2019 ; Hrifech et al, 2020 ; Romaní et al., 2019 ) and/or reduced porosity ( Abdel-Salam et al, 1991 ; Ismail and Stuginsky, 1999 ). Altering either of these parameters in this manner would also lead to an increase in the bed bulk density ( equation (6) ).…”
Section: Resultsmentioning
confidence: 99%
“…Recalling equation (6) , it is seen that the bulk density of a material is a function of its particle density as well as its porosity . Relatedly, it has been reported that the heat load in a packed bed (relative to a set temperature) is increased through use of materials with greater particle density ( Aly and El-Sharkawy, 1990 ; Elouali et al, 2019 ; Hrifech et al, 2020 ; Romaní et al., 2019 ) and/or reduced porosity ( Abdel-Salam et al, 1991 ; Ismail and Stuginsky, 1999 ). Altering either of these parameters in this manner would also lead to an increase in the bed bulk density ( equation (6) ).…”
Section: Resultsmentioning
confidence: 99%
“…The temperature profiles is chosen to validate the model because it represents the dynamic response of the TES at multiple time steps, which embedding the complex heat transfer phenomena within the tank. It provides an illustration about the temperature gradient and thermal stratification within the tank [57], as well as the level of stored and discharged thermal energy [58].…”
Section: Model Validationmentioning
confidence: 99%
“…Thermal energy storage (TES) allows for energy to be stored in the form of heat in times of low or null demand, and used later whenever demand rises [2]. Such technologies aid in the reduction of both carbon footprints and energy costs from small (residential) to big (industrial) scales, being even deemed vital in some applications [4,5]. Such technologies are mostly used in solar energy applications, mainly concentrated solar power plants (CSP) [3,[6][7][8] and solar district heating [9][10][11][12][13], but waste-heat storage systems can also take great advantage of their use [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these that can be highlighted focused on the heat and mass transfer phenomena occurring within packed beds used as thermal energy storage [26]. Abdel-Salam et al established a cylindrical coordinate-based 1D numerical model, through which it was revealed that the increase of bed length improves storage capacity while not affecting the rate of charge [4]. By implementing the finite difference method in models with distinct number of sections, Arias et al investigated the possibility of using them to represent the stratification phenomena seen in experimental tests [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation